Sentiment Analysis on Rupiah Depreciation Against USD Using XGBoost - Indrayuni, Ni Komang Purnama; Desmayani, Ni Made Mila Rosa; Pramawati, I Dewa Ayu Agung Tantri; Sandhiyasa, I Made Subrata; Widiartha, Komang Kurniawan (Politeknik Negeri Batam, 2025)
The depreciation of the rupiah against the United States dollar (USD) affects purchasing power and economic stability. Public responses are widely expressed through social media such as X and Instagram. This study aims to analyze public sentiment using the Extreme Gradient Boosting (XGBoost) algorithm. Data were collected through crawling and scraping, consisting of 13,443 X comments and 11,287 Instagram comments between January 2024 until April 2025. Preprocessing included emoji conversion, cleaning, case folding, normalization, tokenization, stopwords removal, and Stemming. Sentiment labeling was performed using the InSet Lexicon, TF-IDF weighting, and data splitting into 70:30, 80:20, and 90:10. The XGBoost model was trained with parameters: 100 estimators, learning rate 0.1, max depth 6, and subsample 0.8. Results showed accuracies of 74–76% on X data and stable 77% on Instagram. Model evaluation using precision, recall, and F1-score confirmed consistency: precision 0.76% – 0.84%, recall 0.86%–0.88%, and F1-score 0.82%–0.86%, reflecting a balance between accuracy and robustness in detecting sentiments. Sentiment distribution revealed that X is dominated by negative opinions (38%), while Instagram is more positive (41%). These findings confirm the effectiveness of XGBoost in sentiment classification and provide valuable insights for policymakers to design adaptive communication and monetary strategies based on digital public opinion.